"Squeezing the Life Out of Each Day": Emerging Adult Women's Work-Family Expectations in STEM. Issue 1 (February 2022) - Thoman, Sarah E.; Stephens, Amber K.; Robnett, Rachael D.
Work-family conflict can create challenges for women in science, technology, engineering, and math (STEM) careers. Little is known, however, about how young women in STEM reason about future work-family conflict. The current study examines work-family conflict expectations among undergraduate and graduate women in STEM. Participants ( N = 156) responded to open- and closed-ended survey questions about work-family conflict and academic attitudes. Qualitative analyses revealed two orientations relative to work-family conflict. Women with a challenge orientation anticipated work and family strain, whereas women with an opportunity orientation anticipated that balancing work and family would enhance their lives. Women differed in the strategies they planned to employ to resolve future work-family conflict and in their levels of quantitative constructs such as STEM identity. Findings suggest avenues for improving STEM retention such as mentoring interventions with exposure to role models who are balancing work and family.